AGROINFORM — žemės ir miškų ūkio mokslinės techninės informacijos sistema - Zinkevičienė, Julija (Knygotyra, 1991)
Ten socialist countries of COMECON are the members of AGROINFORM. There are many common regularities in the structure and organization of their agricultural and forestry science information.The main peculiarities of information activities, the structure and function of the international system AGROINFORM, the net of national information systems on science and technology, the problems of their coordination are analized in the article. The main sources of information and information publications of all kinds are presented.The analysis of the material shows that activities of the information bodies in AGROINFORM are of wide range. The information flow requires close analysis and qualified document selection. Most socialist countries have developed the systems of bibliographic information, abstracts and survey services. The selective information and current awareness information are widely used.The cooperation with other socialist countries and participation in AGROINFORM may be used by Lithuanian agricultural industry complex.